PENGADILAN HIBRIDA SEBAGAI UPAYA PEACEBUILDING PASCA RUNTUHNYA KEKUASAN KHMER MERAH DI KAMBOJA - Muhammad Rusli Arafat (UIR Law Review, 2023)
The enforcement of international criminal law is an effort to fulfill the international community's sense of justice for serious international crimes. Cambodia came into the international spotlight under Pol Pot. At that time Pol Pot proclaimed Cambodia as a new country under the name Democratic Kampuchea. He referred to 1975 as "Year Zero" which means that everything wants to be built from ground zero by this regime. April 17, 1975 was declared Liberation Day from the ugly and corrupt Lon Nol regime. The research method used is the normative juridical research method. The results showed that hybrid courts are ideal courts in law enforcement against perpetrators of international crimes because they apply two very important aspects, namely aspects of national law and aspects of international law, so that the shortcomings of each legal system can be covered by other systems, so as not to lose the authority of national law and do not apply international law too much